Electrical Impedance Spectroscopic Analysis on Whole Blood Cells to Correlate Severity Level of Ischemic Stroke Patients - Ferhiyan Nabila; Chomsin Sulistya Widodo; Didik Rahadi Santoso (Jurnal Penelitian Pendidikan IPA, 2023)
Measuring the impedance value of biological materials in the form of blood samples has been widely used to determine a person's health status. Ischemic stroke patients in terms of impedance values and correlates with morphological tests on changes in red blood cells. The Electrical Impedance Spectroscopy (EIS) method is applied by providing a blood sample which is detected by electrodes and read using a BIA tool set so that the results are obtained on a laptop. The results obtained from the EIS test are in the form of Bode graphs, Bode phase graphs, Nyquist graphs, and impedance values. The EIS method uses a frequency of 100 Hz to 100 kHz by injecting a current of 10 Î¼A. In this study, the impedance value obtained for normal people was 1058 Î© to 709 Î©, while for ischemic stroke patients with various levels of condition, it was from 517 Î© to 761 Î©. When counting the number of morphological cells in the patient's blood, changes were found ranging from the most cell changes to the least, namely with a value of 44% to 19%. The severity level of ischemic stroke patients obtained based on impedance tests and morphological tests includes the order P4, P5, P3, P2, P10, P21, P15, P19, P1, P6, P13, P18, P14, P17, P16, P20, P12, P11, P8, P7, P9.